Nanosized Graphene/Nafion Hybrid Modified Electrode for Electrochemical Detection of Dopamine - Yusoff, N.; Pandikumar, A.; Marlinda, A.R.; Huang, N.M.; Lim, H.N. (American Scientific Publishers, 2015)
In this study, nanosized graphene/Nafion (G-Nf) hybrids were prepared by a facile two-steps process consisting of ultrasonication followed by hydrothermal treatment and used for the detection of dopamine (DA) in the presence of ascorbic acid (AA), and uric acid (UA). A HRTEM study revealed that the nanosized graphene had a size of ~18 nm after 16 h of hydrothermal treatment. Further, the nanosized graphene were well dispersed in the Nafion (Nf) matrix under the hydrothermal process at 180 °C. The influence of the hydrothermal treatment time on the formation of the G-Nf hybrids was studied. This showed that the G-Nf hybrid formed after 16 h of hydrothermal treatment had a more uniform distribution than the G-Nf composites obtained after 8 h and 24 h of hydrothermal treatment, which tended to agglomerate. These optimized hydrothermal conditions led to the excellent electrochemical detection of DA, with a lower detection limit of about 102 nM (S/N = 3). The results of this study demonstrated that this sample also exhibited an extraordinarily high sensitivity and selectivity to DA despite the interference of AA and UA. The proposed modified electrode also shows a great potential as a sensor for DA detection in real sample analysis using urine sample.